(untitled) (Citizenship in Action: Extension and Culture Magazine, 2024)
The purpose of this article is to discuss about the unauthorized reproduction of works and the like, called plagiarism, exposing the problem encountered when this type of action is practiced by students in the contexts of basic education (from elementary to high school) and also of higher education. The motivations are discussed, as well as the consequences that may arise from this type of practice. Another objective of this article is to present an extension project that was developed with high school classes from public schools around the region of Carangola/MG. The methodology used for the development of this work encompasses the presentation of the theme from the perspective of various scholars, as well as the exposition of the step by step followed in the development of the extension project, with the use of activities that place the student as the subject of the construction of the your knowledge. The results indicate that the study and application of research practices in basic education classrooms are increasingly necessary so that the problem is gradually minimized and does not reach higher education classroom.